Stress, stressors, and substance use: Differential risk for hookah use among African American college students. Issue 2 (2nd April 2020) - Cunningham-Williams, Renee M.; Jones, Brittni D.; Butler-Barnes, Sheretta T.; Wells, Anjanette A.; Williams Woodson, Sha-Lai L.; Johnson, Sharon D.; Pilar, Meagan R.
Abstract: Using differential, multivariable risk models, we assessed the contribution of substance use and stress/traumatic events to hookah use among African American college students ( n = 1, 402) using data from the Fall 2012 American College Health Association-National College Health Assessment (ACHA-NCHA) II. Lifetime hookah use was 24.8%, with 34.2% of lifetime users having done so in the past 30 days. Compared to nonusers, hookah users had significantly higher use rates of alcohol, marijuana, other tobacco, and other drugs. Furthermore, hookah use was more likely among those with cumulative stress, yet less likely among older students. An implication is that prevention messages may need to be tailored for African American college students and particularly target younger students, substance users, and those with cumulative stress. These findings also inform policy discussions regarding hookah use on college campuses.